EFFECTS OF CHRONIC EXPOSURE TO PARACETAMOL AND HIBISCUS SABDARIFFA LINN CALYX EXTRACT ON THE KIDNEY OF MICE - Orji, Blessing Ogechukwu; Obi, Frederick Otunuya; Ibrahim, Maryam (FUDMA Journal of Sciences, 2020)
This study was conducted to evaluate the effects of concurrent administration of aqueous extract of Hibiscus sabdariffa Linn calyx and paracetamol on kidney injury induced by chronic exposure to paracetamol in mice.  The study was carried out over 16 weeks. The animals were grouped into four (4): control (paracetamol and extract free), extract only, paracetamol only and co-administration of paracetamol with extract. The drug and extract were administered orally at 500 and 250 mg/kg body weight respectively by means of an oral gavage. In order to assess kidney function, electrolytes (sodium, bicarbonate, potassium and chloride), urea and creatinine were assessed in serum. Malondialdehyde (MDA) and antioxidant status (superoxide dismutase and catalase activities, and reduced glutathione level) were estimated in kidney homogenate. Histopathological examinations of kidney sections were also carried out on the mice. Paracetamol toxicity was confirmed by significant increase (P â‰¤ 0.05) in urea and creatinine levels along with altered electrolyte concentrations. Co-administration of paracetamol with aqueous extract of Hibiscus sabdariffa Linn calyx significantly (Pâ‰¤ 0.05) reversed the drug-induced alterations close to control, in most of the parameters assayed. The antioxidant activity of the extract is most likely due to its strong scavenging effect on reactive oxygen species and free radicals.
Keywords: Chronic studies, co-administration, Hibiscus sabdariffa Linn calyx extract, kidney, paracetamol.